Analisis Tingkat Literasi Keuangan Mahasiswa Program Studi Pendidikan Ekonomi dan Non Ekonomi - Hamzah Robbani; Anisa Sumarni (Neolectura, 2022)
The aims of this research is to know about the financial literacy index and finding significant differences levels of financial literacy from Economic Education and from Non Economic study programs. This research population are students from Study Programs of Economic also students from Non Economic. The sampling technique that researcher use is Purposive sampling technique, furthermore the number of sample is determine by Slovin technique. The number of the sample in this research is 30 students from Economic Education and 30 students from Non Economic. Descriptive analysis and Paired Sample T-Test are the analysis technique that researcher use for this research. The result of this study showed that students' literacy about financial is on the low category (<60%), moreover it also showed that there is significant differences level of students financial literacy between the two of them.